O discurso de legitimação do direito e da política em Habermas - Sousa, Francisco Pereira de (2011)
Habermas understands the law as the main source of social integration and political legitimacy of modern times. The consensus or intersubjective understanding was understudied by him, like what makes possible the democratic life in society, under the mediation of the law, the fundamental agent in effecting and democratic legitimacy of the measures considered democratic. However, although the law at the national level has promoted the formation of a democratic conscience and the defense of the fundamental rights, with the formation of a legal order with cosmopolitan trend, from a post-national plan, the same it is not possible. In the national plan, the legal planiing provides the certainty of a legal security sustained and defended by the State - that provides the respect for fundamental freedoms necessary to the democratic life. This does not apply internationally. The creation of a cosmopolitan government, as intends by Habermas, will not be effective in the solving of these questions while there to be so profound disparities and inequalities between the different national units concerned. In despite of the habermasian affirmative, the law is not able to possibly the social integration and democratic legitimacy in the international plan. His political theory - based on an ethics or theory of discourse, which places the center of the political process the idea of consensus or understanding between the parts - does not apply to current global political realities, where the power (and not the right) is that imposes or establishes the preponderant rules, interests and values.